Influence of Urban Areas on Surface Water Loss in the Contiguous United States - I. Palazzoli; A. Montanari; S. Ceola (AGU Advances, 2022)
Abstract Urbanization is one of the main drivers of surface water loss, which implies a transition from water to land. However, it is still unclear how urban areas affect the spatial pattern of surface water loss. Here, we use remotely sensed data to analyze and model the decrease of surface water extent and, in particular, the frequency of surface water loss as a function of distance from urban areas across the contiguous United States (CONUS). We employ an exponential distance‐decay model that confirms the presence of a higher frequency of surface water loss in the proximity of human settlements and provides innovative insights on surface water loss patterns at different spatial scales (i.e., river basins, water resource regions, and the CONUS). These spatial patterns are found to be influenced by climatic conditions, with more widely distributed losses in arid regions with respect to temperate and continental climates. Our results provide a new and deeper understanding of the spatial influence of urban areas on surface water loss, which could be effectively integrated in the definition of sustainable strategies for urbanization, water management, and surface water restoration, focused on both human and environmental water needs.